МУСИҚА ТАЪЛИМИДА ХАЛҚ ДОСТОНЛАРИДАН ФОЙДАЛАНИШНИНГ АҲАМИЯТИ - Халилов, Ф. (SCIENCE and SOCIETY, 2019)
The article contains the information about close connection and relations between Uzbek literature and traditions of Uzbek musical school. There has been determined the place of dastans in the realization of tasks.
Keywords: profession of a bakhshi of dastans; music; to write myth; Alpomish; folklore; bakhshi (singer); song; capability; culture; literature; young generation